An Inquiry into Islamic Finance from the Perspective of Sustainable Development Goals - Gundogdu, Ahmet Suayb (European Journal of Sustainable Development, 2018)
Of the 17 Sustainable Development Goals (SDGs) of the United Nations, the first 11 relate directly to Islamic economics and finance. Indeed, they are a perfect fit with the purpose and principles of Islamic finance. Moreover, the Islamic finance industry has contemporary products to address these SDGs. This paper presents current product development and implementation examples of Islamic finance in the context of SDGs. In this regard, success with SDGs can be attained through resource mobilization. Reality suggests that such mobilization requires product development and successful SDG programs. Further, in order to attract resources, SDG programs need to provide convincing results. The most effective programs, as presented in this paper, should be financed with suitably employed resource mobilization tools. Islamic finance can address the first 11 SDGs by harnessing modern resource mobilization products to these programs. Keywords: Sustainable Development Goals (SDGs), Micro Finance, SME Financing, Infrastructure Development, Affordable Housing, International Trade, Complementary Currency, Cash Waqf, Zakat, Economic Empowerment Fund, Crowd Funding.